Effects of bath parameters on structure characteristic of Ni-W Electrodeposited alloy (Journal of the College of Basic Education, 2023)
This study describes the effects of the bath parameters (temperature, current density, additive concentrations and stirring) on tungsten content and microstructures of Ni-W deposits prepared from thiourea-containing bath, on graphite substrate to protect it from oxidation at high temperature. The morphology of the deposits was studied by optical microscope (TEM) and the approximate composition by energy dispersive spectroscopy (EDS).Increasing the concentration of thiourea refining the structure of the deposits, while the increasing in the current density and temperature led to increase the W content with and without stirring.